Constrained data-driven optimal iterative learning control. (July 2017) - Chi, Ronghu; Liu, Xiaohe; Zhang, Ruikun; Hou, Zhongsheng; Huang, Biao
Highlights: The constrained DDOILC and DDOPTPILC are proposed to attain a better performance without violations of constraints. The proposed methods do not depend on the linear model and thus are robust to unknown changes and uncertainties. The optimal learning gain of the proposed constrained methods can be updated iteratively. The constrained-DDOPTPILC outperforms the constrained-DDOILC for a point-to-point tracking. Abstract: A constrained optimal ILC for a class of nonlinear and non-affine systems, without requiring any explicit model information except for the input and output data, is proposed in this work. In order to address the nonlinearities, an iterative dynamic linearization method without omitting any information of the original plant is introduced in the iteration direction. The derived linearized data model is equivalent to the original nonlinear system and reflects the real-time dynamics of the controlled plant, rather than a static approximate model. By transferring all the constraints on the system output, control input, and the change rate of input signals into a linear matrix inequality, a novel constrained data-driven optimal ILC is developed by minimizing a predesigned objective function. The optimal learning gain is unfixed and updated iteratively according to the input and output measurements, which enhances the flexibility regarding modifications and expansions of the controlled plant. The results are further extended to the point-to-point control tasks where the exact tracking performance is required only at certain points and a constrained data-driven optimal point-to-point ILC is proposed by only utilizing the error measurements at the specified points only.